2019
DOI: 10.1002/brb3.1508
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term stability and characteristics of behavioral, biochemical, and molecular markers of three different rodent models for depression

Abstract: Objective:The present study was designed to explore the long-term differences between three mouse models for depression. Method:In the present study, the unpredictable chronic mild stress (UCMS) model, the glucocorticoid/corticosterone model, and the olfactory bulbectomy model were compared at two, three, and five weeks after model induction. Behavioral testing performed included forced-swimming, tail suspension, open-field and elevated plusmaze tests. In addition, 5-hydroxytryptamine (5-HT) and dopamine level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 55 publications
(62 reference statements)
2
12
0
Order By: Relevance
“…These results suggest that in our study, the hyperactivity observed in the OFT did not affect the FST behavior test. The lack of effect in the FST is consistent with other studies in OBX animals ( Zhu et al, 2020 ), although other authors have found an increase in the immobility in this test ( Morales-Medina et al, 2017 ). The variability in this test indicates that the FST is not a representative behavioral domain in the OBX model ( Alcantara et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These results suggest that in our study, the hyperactivity observed in the OFT did not affect the FST behavior test. The lack of effect in the FST is consistent with other studies in OBX animals ( Zhu et al, 2020 ), although other authors have found an increase in the immobility in this test ( Morales-Medina et al, 2017 ). The variability in this test indicates that the FST is not a representative behavioral domain in the OBX model ( Alcantara et al, 2017 ).…”
Section: Discussionsupporting
confidence: 92%
“…On the other hand, in the SPT that detects an anhedonia-like condition, which is a core feature of major depression and characteristic of the OBX model ( Millón et al, 2019 ; Zhou et al, 2019 ), we observed increased anhedonia ( Zhu et al, 2020 ).…”
Section: Discussionmentioning
confidence: 52%
“…These results suggest that in our study, the hyperactivity observed in the open field test (OFT) is not affecting the FST or the TST behaviour test. The lack of effect in the FST is consistent with other studies in OBX animals [ 39 ] although other authors have found an increased in the immobility in this test [ 27 ]. This variability observed in this test indicates that the FST is not a representative behavioural domain in the OBX model [ 32 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar to the previous studies (25,26), from PND28, pups received one of nine trials ( Table 1) every day until the end of the whole study (PND61). Each trial was randomly taken every day, and the same trial was not used twice in a row.…”
Section: Chronic Unpredictable Mild Stress (Cums)mentioning
confidence: 93%